Development, analysis of reliability and validity of the perspective test - Guevara Pino, Angel (2001)
The present study is based on the implications that he/ she has the perspective in the organization of the space and the development of the process cognitive. One worked with a total sample of 973 students that your they study among the 4to - 6to of Primary and 1ro 2do of Secondary belonging to State Educational Centers and Peculiar of the city of Lima. We want to clear the following queries: To know the value of the dependability and of the validity of the Test of Perspective? and also to Point out if the chronological age, does the one generate and does the type of educational center present significant differences in the yield of the Test of Perspective? was the dependability determined with the Method of internal Consistency and the Method of the Halves finding highly significant correlation coefficients, what means that the test presents a High perseverance and menstruation precision. The Concurrent Validity was obtained correlating the Battery of Differential and General Aptitudes-Elementary Level (BADYG-AND) with the Test of Perspective finding significant coefficients, being better the correlation coefficient with the non verbal factor (1.G.Nv) with those sub-tests of Logical Reasoning and Space Aptitude; while for the Validity of construct the Factorial Analysis was used correlating the examined variables, finding three factors by means of the rotation Varimax, which depend on the predominant dimensions in the figures in the presence of two or' more elements of the figures and in the domain of the volume in the figures. When concluding the analysis we have obtained an instrument been worth and reliable, where it was found that there are significant differences in the perspective for chronological age, for I generate and for the type of educational center charts are presented finally by periods of age. for I generate and for type of school where the direct punctuation was transformed to punctuation normalized standard T for the interpretation of the punctuation of the Test of Perspective.